Characterization of the SpraySyn 2.0 burner: Droplet diameters, flame stability and particle sizes - Lang, Peter; Schneider, Nils E.; Huber, Franz; Will, Stefan (Applications in Energy and Combustion Science, 2025)
Spray flame synthesis (SFS) is a promising technique for the production of metal-oxide nanoparticles. However, the processes involved during the synthesis are not yet fully understood. To provide a common workbench for a wide range of investigations, the standardized SpraySyn burners have been introduced. This work presents an in-depth investigation of the improved SpraySyn 2.0 burner, characterizing important droplet, combustion and particle features. The sizes of the droplets produced from an ignited ethanol spray are measured in a range between 20 mm and 45 mm height above the burner (HAB) employing wide-angle light scattering (WALS), revealing much smaller droplets compared to previous SpraySyn 1.0, which eventually leads to faster evaporation. Flame fluctuations are investigated using high-speed imaging of the flame chemiluminescence, indicating a change in fluctuation behaviour compared to the previous burner. WALS is also employed for single-shot in situ size measurements of produced iron-oxide and titanium-dioxide nanoparticles at various HABs ranging from 30 mm to 210 mm, allowing to observe the particle growth. To further assess the properties of the produced particles, extensive TEM measurements for both particle systems are conducted and evaluated. Finally, the influence of flame pulsations on particle size is investigated by coupling chemiluminescence imaging with WALS, yielding no correlation between both.
CRIS-Team Scopus Importer:2025-03-28
Keywords: Droplet size; Flame fluctuations; Flame spray pyrolysis (FSP); Particle size; SpraySyn burner; Wide-angle light scattering (WALS)